1999
DOI: 10.1007/s002130050865
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D 4 receptor antagonist reversal of subchronic phencyclidine-induced object retrieval/detour deficits in monkeys

Abstract: D4 dopamine receptors (DRs) are enriched in the primate prefrontal cortex, a brain region implicated in cognitive processes, and mesoprefrontal dopaminergic systems appear to be involved in modulating some cognitive functions of the prefrontal cortex. Despite anatomical localization of D4 DRs within the frontal cortex, the role of these receptors, specifically, in the regulation of cognition or behavior in primates is unknown. In these studies, we sought to learn whether specific antagonism of D4 DRs would aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 21 publications
5
50
1
Order By: Relevance
“…This was because even a low dose of haloperidol (0.025 mg/kg i.m.) impairs cognitive performance in the monkey PCP model (Jentsch et al, 1999b), whereas 20-50 times this dose is required to elevate DA release in the dorsolateral prefrontal cortex (Youngren et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This was because even a low dose of haloperidol (0.025 mg/kg i.m.) impairs cognitive performance in the monkey PCP model (Jentsch et al, 1999b), whereas 20-50 times this dose is required to elevate DA release in the dorsolateral prefrontal cortex (Youngren et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have examined cognitive effects of D 4 antagonists. Using an object retrieval/detour task in monkeys (a test of frontostriatal function), Jentsch et al (1999) found that behavioral deficits induced by the NMDA antagonist phencyclidine could be reversed with the selective D 4 antagonist NGD94-1. The D 4 -selective antagonist PNU-101,387G has been reported to prevent working memory deficits induced by the benzodiazepine inverse agonist FG-7142 in monkeys (Arnsten et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been a number of previous reports that systemic administration of D4 antagonists can improve performance on tasks dependent on the PFC. For example, administration of the D4 antagonist NGD94-1 in monkeys reverses the phencyclidine-induced impairments on an object retrieval/detour task (Jentsch et al, 1999). Similarly, impairments in working memory induced by FG-7142, a pharmacological stressor that selectively increases PFC DA release, were attenuated by coadministration of the D4-selective antagonist PNU-101,387G (Arnsten et al, 2000).…”
Section: Opposing Effects Of D4 Receptor Agonists and Antagonists On mentioning
confidence: 97%